GhBEE3-Like gene regulated by brassinosteroids is involved in cotton drought tolerance - Chen, Eryong; Yang, Xiaobei; Liu, Ruie; Zhang, Mengke; Zhang, Meng; Zhou, Feng; Li, Dongxiao; Hu, Haiyan; Li, Chengwei (Frontiers in Plant Science, 2022)
Brassinosteroids (BRs) are important phytohormones that play a vital role in plant drought tolerance, but their mechanisms in cotton (Gossypium hirsutum L.) are poorly understood. Numerous basic helix-loop-helix (bHLH) family genes are involved in the responses to both BRs and drought stress. GhBEE3-Like, a bHLH transcription factor, is repressed by both 24-epi-BL (an active BR substance) and PEG8000 (drought simulation) treatments in cotton. Moreover, GhBZR1, a crucial transcription factor in BR signaling pathway, directly binds to the E-box element in GhBEE3-Like promoter region and inhibits its expression, which has been confirmed by electrophoretic mobility shift assay (EMSA) and dual luciferase reporter assay. Functional analysis revealed that Arabidopsis with GhBEE3-Like overexpression had drought sensitive phenotype, while GhBEE3-Like knock-down cotton plants obtained by virus-induced gene silencing (VIGS) technology were more tolerant to drought stress. Furthermore, the expression levels of three stress-related genes, GhERD10, GhCDPK1 and GhRD26, were significantly higher in GhBEE3-Like knock-down cotton than in control cotton after drought treatment. These results suggest that GhBEE3-Like is inhibited by BRs which elevates the expressions of stress-related genes to enhance plant drought tolerance. This study lays the foundation for understanding the mechanisms of BR-regulated drought tolerance and establishment of drought-resistant cotton lines.